Effects of Fertilizer, Fertilizer, Compost, Mycorrhiza and Bacteria - Seda Bice Ataklı; Sezer Şahin; Sabriye Belgüzar (Turkish Journal of Agriculture: Food Science and Technology, 2021)
One of the most important factors that increase soil fertility is the amount of soil organic matter. One of the ways to increase soil organic matter is the addition of organic fertilizers. Yemsoy soybean cultivar was used in the study, and pot study was carried out in 3 replications according to the randomized blocks experimental design. In the study, three different fertilizer doses (EC 0- 0.5- 1), three different grape pomace compost (0- 20-40 %) were applied to the peat perlite mixture, and mycorrhiza and bacteria inoculation to these environments. At the end of a 60-day growing period, the plants were harvested from the top of the pot, and measurements were made. In the study, there was an increase in the above-ground fresh and dry weights, root fresh, and root dry weights of soybean plants grown with increasing fertilizer rates. The addition of compost to the growing medium, the addition of mycorrhiza, and bacteria caused different results in the investigated properties. The increase in compost and plant nutrition doses was effective in increasing plant growth.